2011
DOI: 10.2478/s11687-011-0039-x
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of root-knot nematodes in potting mixes amended with different composted biowastes

Abstract: 278 SummarySuppressiveness of soil amendments with different rates of composted biowaste materials, olive pomace, municipal green wastes, sewage sludge and spent mushroom substrate, was evaluated against the root-knot nematode Meloidogyne incognita on tomato in potting mixtures. Soil amendments were applied at 0, 10, 25, 50 and 100 g kg -1 soil, according to a randomized block design with five replications for each treatment. Sixty days after tomato transplanting, nematode population density on plant roots and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…Our results were agreed and supported with many studies emphasized that the root-knot nematodes were greatly suppressed after MC application [24,[54][55][56]. They found that MC was effective as soil amendments in the management of Meloidogyne spp.…”
Section: Resultssupporting
confidence: 92%
“…Our results were agreed and supported with many studies emphasized that the root-knot nematodes were greatly suppressed after MC application [24,[54][55][56]. They found that MC was effective as soil amendments in the management of Meloidogyne spp.…”
Section: Resultssupporting
confidence: 92%
“…A lot of investigations have been made about utilizing many plant residues and agro-industrial wastes as organic soil amendments or pre planting soil biofumigants in the management of plant-parasitic nematodes and other plant pathogens were carried out by many authors (Akhtar and Alam, 1993;Ploeg and Stapleton. 2001;Mashela, 2002;Bailey and Lazarovits, 2003;López-Pérez et al, 2005;Piedra Buena et al, 2006Monfort et al, 2007;Hassan et al, 2010;López-Pérez et al, 2010;D'Addabbo et al, 2011;El-Nagdi and Abd Elfattah, 2011;Khattak and Khattak, 2011;Anita, 2012;Chindo et al, 2012;Karavina and Mandumbu, 2012;Masheva et al, 2012;Aslam and Saifullah, 2013;Kruger et al, 2013 andYoussef andLashein, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been carried out to evaluate the effectiveness of control strategies at low environmental impact alternative to chemicals. A wide range of options was considered: amendments, biofumigations, crop rotation, grafting, green manures, mycorrhization, resistant cultivars HELMINTHOLOGIA, 49, 4: 259 -269, 2012 Nematicidal and fertilizing effects of chicken manure, fresh and composted olive mill wastes on organic melon (Gamliel et al, 2000;Sasanelli et al, 2002;Nico et al, 2004;Castillo et al, 2006;D'Addabbo et al, 2011;Renčo et al, 2007;, soil solarization, ozone and steam applications (Sasanelli & Greco, 2000;Tamietti & Valentino, 2000;Tjamos et al, 2000;, biocidal plants or natural byproducts (Gommers, 1981;Grainge & Ahmed, 1988;Sasanelli & D'Addabbo, 1993;Sasanelli et al, 2007Sasanelli et al, , 2009Maistrello et al, 2010;Renčo et al, 2012) and biological control agents especially fungi and bacteria (Vannacci & Gullino, 2000;. Soil amendments, commonly used in organic farming, are effective in the management of several soil borne plant pathogens and phytoparasitic nematodes (Nico et al, 2004) and at the same time can improve soil fertility as well as productivity and quality of plant products (Bulluck et al, 2002;Rivera & Aballay, 2008).…”
Section: Introductionmentioning
confidence: 99%